Cost Effectiveness of Cladribine Tablets for the Treatment of Relapsing-Remitting Multiple Sclerosis in The Netherlands - Michels, Renée Else (Appl Health Econ Health Policy, 2019)
BACKGROUND: Cladribine tablets have recently become available in The Netherlands for patients with relapsing–remitting multiple sclerosis (RRMS) as a disease-modifying agent that reduces the frequency and severity of relapses and delays disability progression. OBJECTIVE: The aim of this study was to evaluate the cost effectiveness of cladribine tablets, compared with alternative options, in the treatment of RRMS patients with high disease activity (HDA) and patients with rapidly evolving severe (RES) MS in The Netherlands. METHODS: A Markov model was developed simulating the costs and effects of RRMS treatment. For HDA, alemtuzumab and fingolimod were used as comparators; natalizumab was used for the RES subpopulation. The analysis included a societal perspective and a value-of-information (VOI) analysis. RESULTS: For the HDA subpopulation, treatment with cladribine tablets was the cost-effective (dominant) strategy compared with alemtuzumab and fingolimod, with 50.9% and 98.2%, respectively, probability of being cost effective at a threshold of €50,000/QALY gained and a net monetary benefit (NMB) of €10,866 and €151,115, respectively. For the RES subpopulation, treatment with cladribine tablets dominated treatment with natalizumab, with 94.1% probability of being cost effective at a threshold of €50,000/QALY gained and an NMB of €122,986. Note that these outcomes are driven by the lower costs of cladribine tablets. Efficacy differences were small, very uncertain, and likely not clinically meaningful. The probabilistic sensitivity analyses showed significant overlap in the credible intervals for total lifetime QALY outcomes and costs of cladribine tablets and all relevant comparators. The population-level VOI amounted to €19,295,441. CONCLUSIONS: The base-case analysis shows that treatment of RRMS with cladribine tablets is cost effective versus alemtuzumab and fingolimod in HDA patients, and cost effective versus natalizumab in RES patients, at a threshold of €50,000. Driven by the lower costs, cladribine tablets were cost effective (dominant) in all base-case analyses. However, given that outcomes are based on indirect comparisons and post hoc subgroup analysis, as well as the uncertainty surrounding the outcomes, the results presented in this paper should be interpreted with caution. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s40258-019-00500-8) contains supplementary material, which is available to authorized users.